IMPACT OF ECONOMIC GROWTH AND GLOBALIZATION ON INCOME INEQUALITY POPULATION IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2015)
The article deals with globalization and economic growth as factors affecting the distribution of income inequality in the population of the Republic of Kazakhstan. Statistically, the hypothesis is confirmed for the Kuznets Kazakhstan.